2020
DOI: 10.1088/1742-6596/1700/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Learning Media’s “Tutorial Video for Setting the Front Wheel Alignment With a 3D Spooring Tools” at SMK N 1 Magelang

Abstract: This study aims to: (1) Produce a learning media’s tutorial video for setting the Front Wheel Alignment with a 3D Spooring tool; (2) find out the feasibility of developing a tutorial video for setting the Front Wheel Alignment with a 3D Spooring tool for learning media on Light Vehicle Engineering Department in Vocational High School 1 Magelang. The type of this research is Research and Development (R&D) using the 4D model (define, design, develop, disseminate) because more clearly the steps in each stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Additionally, the usability level of AR-based circuit practice was confirmed through Equation ( 1). From the usability score of 87% (percentage of eligibility), it was confirmed that the utilization of AR in circuit practice was highly effective for trainees (Arifin & Maharani, 2021;Prihantono et al, 2020;Widoyoko, 2012) (as shown in Tab. 2).…”
Section: Fig 10 a Percentage Of Usability Parameters Resultsmentioning
confidence: 76%
“…Additionally, the usability level of AR-based circuit practice was confirmed through Equation ( 1). From the usability score of 87% (percentage of eligibility), it was confirmed that the utilization of AR in circuit practice was highly effective for trainees (Arifin & Maharani, 2021;Prihantono et al, 2020;Widoyoko, 2012) (as shown in Tab. 2).…”
Section: Fig 10 a Percentage Of Usability Parameters Resultsmentioning
confidence: 76%